The role of the media in shaping the environmental awareness of the Yemeni public – Empirical Study - Othman, Nadmih Abdulsalam (Journal of Humanities & Social Sciences, 2022)
The subject of media has received the attention of many thinkers, academics and researchers due to its role in arousing public interest in the issues and problems at hand. Therefore, this research sought to identify the role of the media in shaping the environmental awareness of Yemeni society. Its importance stems from the fact that it may contribute to understanding the nature of the media’s role in influencing the public in Yemen. The social survey method was used on the consideration of being the most appropriate research method for such research. A questionnaire encompassing four axes aimed at identifying the habits and patterns of the public’s use of these means and the achieved gratifications and measuring and evaluating the role of the media in creating environmental awareness was prepared. Besides, a fifth axis is added, containing the socio-demographic data for the respondents. The questionnaire was applied on a sample of 200 individuals after verifying its validity and reliability through the verb "repetition of consistency." After collecting and then analyzing the data, this research has come with major findings, most notably the deficiencies by (55%) in the role of the Yemeni media of its various means in the environmental awareness efforts, which resulted in weak environmental awareness among the Yemeni public in terms of the environmental protection. The interest rate in media coverage of the environmental issues was (16.5%), compared to (69%) for the political issues.
Keywords: Media; Mass Communication; Environmental Awareness; the Public; Motives